Determining Water Quality Status and Assimilation Capacity of Pollutant Loads in West Lombok Regency - M Said Ramdlan; Astrini Widiyanti; Hilman Rizkiadi; Muhamad Arif Sidiq; Khaerul Ihwan (Universitas Diponegoro, 2024)
Babak watershed is one of the essential watersheds in Lombok Island providing water supply for irrigation, fish pool, drinking water supply, and micro-hydro power plant. Excessive human activities degrade the water quality of Babak watershed, and more pollutants are present in the water column. Thus, this study aims to determine Babak watershed's water quality status and assimilating capacity to plan effective and holistic mitigation measures properly. The study calculates the pollution index (PI) using a formula based on the Minister of Environment No.115/2003 Decree and assimilating capacity (AC) based on the Minister of Environment No.110/2003 Decree. The results found that Babak watershed is lightly polluted, defined by exceeding chemical parameters such as DO, total phosphate, nitrite, and dissolved iron (Fe). Similarly, these parameters (total phosphate, nitrite, and Dissolved iron (Fe) also reached the maximum assimilation capacity of Babak watershed to contain and self-purify these pollutants from the water column. Thus, planning mitigation and adaptation measures are required to prevent further contaminations in this watershed.